Instrumentation issues and problems in earth dams (Case Study; Shah Qasim Dam in Yasouj, Iran) - Behshad, Amir (Nexo Revista Científica, 2020)
Installation and monitoring of instrumentation is one of the practical methods for controlling safety and stability of earth dams. Piezometers existing in dam body and dam abutments are one of the various types of precision instruments used in dams, which indicate the height of water level in different parts of the dam. In order to evaluate the performance of piezometers of Shah Qasim Dam in Kohgiluyeh and Boyerahmad province (in south east of Iran), we compare water level changes in piezometer and water level changes in the dam lake over time. In this paper, the above mentioned dam is modelled using the SEEP/W software, then after imposing boundary conditions, water levels are computed at various points. For more accurate comparison, water level changes are plotted in transverse and longitudinal piezometers over time. The results of analysis indicate significant increase of permeability in vicinity of some piezometers. The piezometers BX4, BX14, BX13 and SP6, and the region near them, as well as piezometers SP24 and SP18 and their surrounding area, have critical conditions which should be inspected as soon as possible.